2018
DOI: 10.3233/cbm-171109
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of hsa_circ_0001649 in hepatocellular carcinoma predicts a poor prognosis

Abstract: Hsa_circ_0001649 could act as a novel prognostic biomarker for HCC patients. In addition, hsa_circ_ 0001649 might be a potential therapeutic target for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Xie Y et al 28 found that hsa_circ_0074362 probably plays a role in the initiation of gastric cancer and may be a potential biomarker of gastric cancer. Zhang X et al 29 showed that hsa_circ_0001649 could act as a novel prognostic biomarker and a potential therapeutic target for hepatocellular carcinoma patients. Besides, Yang F et al 30 found that circular RNA circ-LDLRAD3 could be a biomarker in diagnosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Xie Y et al 28 found that hsa_circ_0074362 probably plays a role in the initiation of gastric cancer and may be a potential biomarker of gastric cancer. Zhang X et al 29 showed that hsa_circ_0001649 could act as a novel prognostic biomarker and a potential therapeutic target for hepatocellular carcinoma patients. Besides, Yang F et al 30 found that circular RNA circ-LDLRAD3 could be a biomarker in diagnosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis suggests SHPRH-146aa protects SHPRH protein from degradation by the ubiquitin proteasome. Another recent studies indicated that circSHPRH was identified as a biomarker in hepatocellular carcinoma [104,105]. It is therefore reasonable to speculate that circSHPRH has the potential to be translated in other human cancers.…”
Section: Translation Of Circshprh In Gliomamentioning
confidence: 96%
“…It has been documented that some circRNAs exert their biological functions both through encoded peptides and by RNA-based regulatory mechanism. For example, circ-SHPRH can encode SHPRH-146aa peptide to suppress tumorigenesis in glioma [96], and it can function as miRNA sponge to inhibit HCC progression [104,105]; circZNF609 can act as miRNA sponge to promote breast cancer progression [25], and it can encode protein in Myogenesis [60]. Some circRNAs are bi-functional in human cancer, and the bi-functional ability of circRNAs remains to be explored.…”
Section: Future Perspectivementioning
confidence: 99%
“…CircRNA is involved in various biological processes, including HCC cell proliferation, apoptosis and metastasis (11). For instance, overexpression of Homo sapiens circRNA_0001649 inhibits the proliferation and invasion of HCC cells (12). CircRNA circMTO1 (mitochondrial tRNA translation optimization 1) inhibits HCC progression by acting as a sponge for miRNA-9.…”
Section: Introductionmentioning
confidence: 99%